FOREST FIRE ANALYSIS FROM PERSPECTIVE OF SPATIAL-TEMPORAL USING GSTAR (p;λ_1,λ_2,…,λ_p) MODEL - Pratiwi, Hesty; Imro'ah, Nurfitri; Huda, Nur'ainul Miftahul (PATTIMURA UNIVERSITY, 2025)
West Kalimantan is particularly susceptible to the devastating effects of forest fires, among the natural disasters that have a significant impact. One of the indicators that can be used to identify forest fires is the presence of hotspots. The term